The Effect of Zinc Supplementation on Glycemic, Weight, and Blood Pressure Control in Patients With Type 2 Diabetes Mellitus: A Double‐Blind Randomized Controlled Trial - Mehrab Sayadi; Sara Javadpour Nowbandegani; Fatemeh Balaghi Inalou; Bahman Nazemzadegan; Shirzad Javidi Alsaadi; Mohammadreza Eskandari; Matin Sepehrinia (Health Science Reports)
ABSTRACT Backgrounds and Aims Type 2 diabetes and its complications are assumed to be major public health problems globally. Zinc is one of the elements that play a part in insulin secretion and signaling. Therefore, this study seeks the answer to the following question: “What are the effects of 220 mg zinc sulfate supplementation on the weight, blood pressure, and glycemic control of patients with Type 2 diabetes?”. Methods In this randomized controlled double‐blind trial, 79 patients with Type 2 diabetes were allocated into two groups through permuted block randomization method. The study group received two capsules of 220 mg of zinc sulfate containing 50 mg of zinc, and the control group received two capsules of 220 mg of placebo ingredient per week for 12 weeks. At the start and end of the treatment period, the fasting blood glucose (FBG), glycated hemoglobin (HbA1c), zinc level, weight, waist circumference (WC), and blood pressure were measured. Results After 12 weeks of follow‐up, 72 patients completed the study. There were no significant differences before and after the intervention in the FBG, HbA1c, zinc levels, and WC between the two groups. Intragroup analysis showed that weight and body mass index increased in the intervention group; however, these changes were not significant in comparison to the control group. Also, diastolic blood pressure significantly increased in the control group; however, changes in systolic blood pressure were not significant in both groups. Conclusion Taking 220 mg of zinc sulfate supplement twice a week did not show significant benefit for weight, blood pressure, and glycemic control in patients with Type 2 diabetes. Trial Registration This trial was registered on the Iranian Registry of Clinical Trials (IRCT) website with code number 29627 on September 18, 2018.